Priorities of improving the competitiveness of higher education in regional development management (case of Ukraine) - Гринькевич, О. С.; Сорочак, О. З.; Hrynkevych, O.; Sorochak, O. (Видавництво Львівської політехніки, 2023)
Мета статті – перевірити гіпотезу про істотність відмінностей у показниках розвитку регіональних систем вищої освіти в Україні та обґрунтувати пріоритетні напрями підвищення їх конкурентоспроможності за критеріями якості, соціальної відповідальності та економічної ефективності. Автори обґрунтовують концептуальну модель для аналізу конкурентоспроможності системи вищої освіти за критеріями якості, економічної відповідальності та економічної ефективності, визначають перелік відповідних показників для їх вимірювання, а також пропонують результати аналізу систем вищої освіти в 25 регіонах України. Для дослідження використано основні положення теорій людського, соціального, інтелектуального капіталу, теорії стейкхолдерів, міждисциплінарний підхід, методи і показники статистичного аналізу. Результати дослідження підтвердили гіпотезу про значні дисбаланси в розвитку регіональних систем вищої освіти в Україні, зокрема за такими показниками, як співвідношення абітурієнтів ЗВО та випускників середніх шкіл, які беруть участь у зовнішньому незалежному тестуванні в цьому регіоні, частка студентів, які навчаються за рахунок коштів місцевих бюджетів, кількість українських ЗВО у міжнародних рейтингах університетів. Зазначені дисбаланси спричиняють істотні стратегічні втрати людського та інтелектуального капіталу регіонів України, позначаються на їхньому інноваційному розвитку. Практична значущість отриманих результатів полягає у тому, що запропоновано пріоритетні напрями підвищення конкурентоспроможності вищої освіти в регіонах України, які можуть бути використані для досягнення стратегічних цілей регіонального розвитку в частині реалізації інтелектуального потенціалу та підвищення конкурентоспроможності економіки.

Purpose. This article aims to test the hypothesis of significant imbalances in the regional higher education systems in Ukraine and to substantiate the priority areas for improving their competitiveness on the criteria of quality, social responsibility, and economic efficiency. Design/methodology/approach. The first part of the study offers a conceptual model for analysing the higher education system's competitiveness. The authors use the main provisions of the theory of human, social and intellectual capital, stakeholder theory, literature review method, and interdisciplinary approach to determine the features of higher education as a particular sector of social activity, regional economy, as well as an object of competitiveness analysis in terms of three criteria – quality, economic efficiency, and social responsibility. In the second part, the authors propose the methodological framework and list of indicators for analysing the regional higher education systems based on a developed conceptual model. The third part presents the results of statistical analysis of higher education systems in 25 regions of Ukraine and priority areas for improving their competitiveness by the criteria of quality, social responsibility, and economic efficiency. Findings. The hypothesis of significant imbalances in the regional higher education systems in Ukraine is proven. The results of the analysis reveal substantial differences in the regional higher education systems, particularly for indicators as the ratio of university entrants and high school graduates participating in the independent external testing in this region, the proportion of HEIs students studying at the expense of local budgets, the number of regional HEIs in the world university rankings. Considering the results of the analysis and the features of regional development, the authors substantiate the priority areas for improving the competitiveness of the higher education system for Ukraine’s regions by the criteria of quality, social responsibility, and economic efficiency. Each of these priority areas involves using appropriate target indicators and considers the interests of key stakeholders of the higher education system. Practical implications. The authors propose priority areas for improving the competitiveness of higher education in the regions that can be used to implement the strategic goals of the potential intellectual development of Ukraine’s regions and thus enhance the role of HEIs in solving urgent problems of regional development. Originality/value. Despite numerous papers on economics and management in higher education, there are virtually no studies in academic practice, which aim to take into account the regional features of higher education. Secondly, based on its comprehensive empirical research, third, it can justify the strategic priorities for the development of provincial higher education systems with relevant target indicators. Thus this study aims to fill these gaps.
Про пріоритети підвищення конкурентоспроможності вищої освіти в управлінні регіональним розвитком (приклад України)
Keywords: вища освіта; конкурентоспроможність; якість; соціальна відповідальність; економічна ефективність; регіон; Україна; higher education; competitiveness; governance; quality; social responsibility; economic efficiency; region; Ukraine; 33.021; [378.014.5; 005.332.4(477)